OTOMASI SISTEM PELETAKAN DAN PENGAMBILAN BARANG PADA RAK BERBASIS PROGRAMMABLE LOGIC CONTROLLER - Mulyadi, Melisa; Sutrisno, Bobby (Teknik dan Ilmu Komputer, 2012)
Every factory absolutely had a stock room from production. Generally for processing to put on and put out the object from the rack, the factory usually had using a human power. Human error cause a trouble working. Human error could make the lack of production process. So automation system to put on and put out the object from the rack is needed. In this system, Programmable Logic Controller (PLC) is implemented ÃÂ to control the process. From this experiment, the process of put on and put out the object from the rack can be working well with their size and the result is the system can not found mistake from the processing.ÃÂ Keywords: programmable logic controller, limit switch, ladder diagram, DC motor, relay